Pariwisata Halal Desa Wisata Dayun Provinsi Riau : Strategi dan Upaya Pengembangan - Annisa Agelina; Zulkarnain Muhammad Ali; Indra Indra (ITB AAS INDONESIA Surakarta, 2025)
Objective : The purpose of this study is to investigate the problems of halal tourism development especially tourism village in Riau Province, Indonesia along with the solutions, potentials and also the best strategy to use. Method : The research method used in this study is Analytic Network Process (ANP). Informants are experts in the field of halal tourism. This study involves 5 (five) informants consisting of regulators, academia, and practitioner. Finding : The results showthat the main potential that will be increase in halal tourism Dayun tourism village is creative economic sector, while the main problem is the lack of innovation. In terms of solutions, the lokal tourism regulation provided by the government is themain solution to enchance lokal halal tourism And the first strategy is to be need competitive human resources. From these results, the government can consider to improve human resources skill in every region of tourism so there will be competitive human resources in order to developing sustainable halal tourism